Digital literacy gaps in promoting 21st century skills among students in higher education institutions in Sub-Saharan Africa: a systematic review - Placidius Ndibalema (Cogent Education)
This study examined digital literacy gaps impacting the promotion of the 21st century skills among students in higher education institutions in sub-Saharan Africa. As many institutions undergo technological transformations, understanding these gaps is crucial for equipping graduates with the required digital workforce skills. The review synthesized findings from 14 empirical studies published between 2016 and 2023 using content analysis through Atlas.ti software to identify patterns. Key findings revealed that 21st century skills are insufficiently developed due to inadequate digital infrastructure and unprepared lecturers. Additionally, outdated or nonexistent ICT policies hinder the effective adoption of technology in teaching. The study calls for reforms in curricula to prioritize digital solutions and enhance professional development for educators. Improved digital literacy is vital for preparing students for the job market and fostering broader socio-economic development in sub-Saharan Africa. Future research should investigate long-term trends and evaluate the effectiveness of digital literacy initiatives across varied educational contexts.